Kingdom through covenant : a biblical-theological understanding of the covenants - Gentry, Peter John (Crossway, 2018)
Kingdom through Covenant is a careful exposition of how the biblical covenants unfold and relate to one another--a widely debated topic, critical for understanding the narrative plot structure of the whole Bible. By incorporating the latest available research from the ancient Near East and examining implications of their work for Christology, ecclesiology, eschatology, and hermeneutics, scholars Peter J. Gentry and Stephen J. Wellum present a thoughtful and viable alternative to both covenant theology and dispensationalism. This second edition features updated and revised content, clarifying key material and integrating the latest findings into the discussion.